RONs Revisited: General Approach to Model Reconfigurable Object Nets based on Algebraic High-Level Nets - Ermel, Claudia; Shareef, Sarkaft; Fischer, Winzent (Electronic Communications of the EASST, 2011)
Reconfigurable Object Nets (RONs) have been implemented in our group to support the visual specification of controlled rule-based transformations of marked place/transition (P/T) nets. RONs are high-level nets (system nets) with two types of tokens: object nets (P/T nets) and net transformation rules. System net transitions can be of different types to fire object net transitions, move object nets through the system net, or to apply a net transformation rule to an object net. The disadvantage of the RON approach and tool is the limitation of object nets to P/T nets and the limitation of the underlying semantics of RONs due to the fixed types for system net transitions. Often, a more general approach is preferred where the type of object nets and the behavior of reconfigurations may be defined in a more flexible way. In this paper, we propose to use Algebraic High-Level nets with individual tokens (AHLI nets) as system nets. In this more general approach, tokens may be any type of Petri nets, defined by the corresponding algebraic signature and algebra. To support this general approach, a development environment for AHLI nets is currently implemented which allows the user to edit and simulate AHLI nets. We present the formalization of RONs as special AHLI nets and describe the current state of the AHLI net tool environment.